Targeting Tregs in Malignant Brain Cancer: Overcoming IDO - Lesniak, Maciej (Frontiers in Immunology, 2013)
One of the hallmark features of glioblastoma multiforme (GBM), the most common adult primary brain tumor with a very dismal prognosis, is the accumulation of CD4+CD25+Foxp3+ regulatory T cells (Tregs). Regulatory T cells (Tregs) segregate into two primary categories: thymus-derived natural Tregs (nTregs) that develop from the interaction between immature T cells and thymic epithelial stromal cells, and inducible Tregs (iTregs) that arise from the conversion of CD4+FoxP3- T cells into FoxP3 expressing cells. Normally, these Treg subsets complement one another’s actions by maintaining tolerance of self-antigens, thereby suppressing autoimmunity, while also enabling effective immune responses towards non-self-antigens, thus promoting infectious protection. However, Tregs have also been shown to be associated with the promotion of pathological outcomes, including cancer. In the setting of GBM, nTregs appear to be primary players that contribute to immunotherapeutic failure; ultimately leading to tumor progression. Several attempts have been made to therapeutically target these cells with variable levels of success. The blood brain barrier-crossing chemotherapeutics, temozolomide and cyclophosphamide, vaccination against the Treg transcriptional regulator, FoxP3, as well as mAbs against Treg-associated cell surface molecules CD25, CTLA-4 and GITR are all different therapeutic approaches under investigation. Contributing to the poor success of past approaches is the expression of indoleamine-2,3-dioxygenase 1 (IDO), a tryptophan catabolizing enzyme overexpressed in GBM and critically involved in regulating tumor-infiltrating Treg levels. Herein, we review the current literature on Tregs in brain cancer, providing a detailed phenotype, causative mechanisms involved in their pathogenesis and strategies that have been used to target this population, therapeutically.